2016
DOI: 10.1097/md.0000000000005016
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hospitalization for hypoglycemia among older Korean people with diabetes mellitus

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 29 publications
6
27
1
Order By: Relevance
“…Participant numbers ranged from 96 to 892,223. There were 28 longitudinal cohort studies [18, 21, 28, 29, 3237, 4057] and 13 cross-sectional studies [17, 19, 20, 2227, 30, 31, 38, 39]. All included studies were conducted in high or upper-middle-income countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participant numbers ranged from 96 to 892,223. There were 28 longitudinal cohort studies [18, 21, 28, 29, 3237, 4057] and 13 cross-sectional studies [17, 19, 20, 2227, 30, 31, 38, 39]. All included studies were conducted in high or upper-middle-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…The measure of MM condition count used in the included studies varied considerably. The majority of studies (24/41 (59%)) [19, 21, 27, 28, 3037, 3941, 43, 46, 49–53, 55, 57] measured MM in terms of the Charlson Comorbidity Index (CCI) [9]. MM was represented as a simple count of conditions that were available in the study datasets in 15 studies (32%) [17, 18, 22–25, 29, 38, 44, 47, 48, 50, 52, 54, 56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have established that comorbidities such as cardiovascular diseases and chronic kidney diseases increase the risk of hypoglycaemic events. 23 Likewise, the use of cardiovascular system medications (eg, aspirin, angiotensin receptor blocker, calcium channel clocker, beta-blocker and ACE inhibitors) was common across the study cohort and could have contributed to increasing the hypoglycaemic risk. 24 25 …”
Section: Discussionmentioning
confidence: 99%
“…After further evaluating the 135 originally selected articles, 50 high-quality (i.e., had 5–9 points on the NOS, Table 1 ) [ 17 ] articles describing observational studies were included in this study. The remaining 85 articles were excluded for the following reasons: there were no necessary data on insulin concentrations [ 13 , 18 – 27 ]; related genes and insulin signaling pathway proteins were the main study outcomes [ 28 – 36 ]; there was no clear description or record of a cognitive function evaluation [ 37 – 42 ]; the design of the experiments was unreasonable for the purpose of this study [ 43 – 52 ]; the experimental methods were incomplete [ 53 – 60 ]; the papers did not provide completely related data [ 61 – 66 ]; data from only one group were reported [ 2 , 67 74 ]; the papers reported data from the same cohort of patients who were used in another study [ 75 – 81 ]; insulin levels were reported in patients with comorbid diseases (in addition to diabetes, metabolic syndrome and related diseases can also lead to nonpsychotic dementia [ 82 – 89 ]), such as cognitive dysfunction caused by depression or anxiety [ 85 ]; serum insulin was measured before and after insulin treatment or other treatments that could influence insulin metabolism in patients with nonpsychotic dementia; only changes in the MMSE scores before and after the treatment were analyzed, while differences between the observation group and the control group were not analyzed [ 11 , 12 ]; and the studies involved cell experiments [ 90 ] or animal experiments [ 6 , 91 – 96 ] (for the flowchart, see Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%